Intersecting where? The multi-scalar contextual embeddedness of intersectional entrepreneurs. Issue 9 (20th October 2022) - Yamamura, S.; Lassalle, P.; Shaw, E.
ABSTRACT: We explore the experiences of LGBT* ethnic minority entrepreneurs, their changing locations and their entrepreneurial activities. Using a unique mixed-method approach which collected empirical data from Germany and the Netherlands, the paper combines an ethnographic fieldwork of intersectional entrepreneurs, community activists and policy-makers with an original survey with LGBT* customers. Our findings contribute to understanding of intersectionality by revealing the role played by the contextualized embeddedness of intersectional entrepreneurs at the different geographic scales of supranational, national, regional and inter and intra-urban. While such embeddedness frames the challenges they face, it also provides opportunities for intersectional entrepreneurs. Using a multi-scalar perspective, this paper delivers a spatially contextual perspective of entrepreneurial diversity and provides a framework to analyse the complex issues and contexts with which intersectional entrepreneurs are both confronted and embedded within. This paper contributes to refining the spatial context of entrepreneurship which has gained attention in recent studies of entrepreneurship and regional development. The paper responds to a call for gender entrepreneurship scholars to contribute to understanding of intersectional entrepreneurship. Finally, this study goes beyond the binary view of female migrant entrepreneurship by adopting a more gender diverse lens which considers the experiences of LGBT* entrepreneurs from ethnic minorities.